Gifted Tongues : High School Debate and Adolescent Culture. - Fine, Gary Alan (Princeton University Press, 2008)
Learning to argue and persuade in a highly competitive environment is only one aspect of life on a high-school debate team. Teenage debaters also participate in a distinct cultural world--complete with its own jargon and status system--in which they must negotiate complicated relationships with teammates, competitors, coaches, and parents as well as classmates outside the debating circuit. In Gifted Tongues, Gary Alan Fine offers a rich description of this world as a testing ground for both intellectual and emotional development, while seeking to understand adolescents as social actors. Consid.